Rancang Bangun Alat Indikator Suhu Pada Chamber - Adik Susilo Wardoyo; Farhan Tri Saputra (Prodi D3 Teknik Elektronika Politeknik Gajah Tunggal, 2026)
The mixing process of materials in the manufacture of compounds in the tire industry is highly dependent on the temperature stability in the mixer chamber. Operators' lack of knowledge about the actual chamber temperature often causes MV (Mooney Viscosity) problems, which affect the quality of the compound. One of the causes is the lack of a real-time temperature monitoring system. To address this issue, a temperature indicator device was designed and developed, equipped with a type-K thermocouple sensor, temperature controller, Arduino, and a visual alarm system. One of the key focuses in developing this device was the design and strength of the sensor mounting frame and panel. The frame was designed using ASTM A36 and AISI 304 materials, and its strength was analyzed in terms of load and welded joints. Test results showed that the device operates stably and safely, and the frame can support the entire system effectively. With this device, temperature monitoring of the chamber becomes more effective, and the potential for MV issues can be significantly reduced.